Evaluasi Implementasi Petunjuk Teknis Komisi Pengawas Pupuk Dan Pestisida Di Kabupaten Solok Sumatera Barat - Yosalli, Yosalli; Siswati, Sri; Fitria, Friska Eka (JESS (Journal of Education on Social Science); Vol 9 No 3 (2025): General Issues on Public Service, 2025)
The agricultural sector is one of the backbones of national development, playing a vital role in ensuring food security, creating jobs, and improving public welfare. However, increasing productivity in modern agriculture, which relies on the use of chemical fertilizers and pesticides, presents challenges to human health and environmental sustainability. The Indonesian government has established the Fertilizer and Pesticide Supervisory Commission (KPPP) as an institution tasked with overseeing the distribution and use of agricultural chemicals through Technical Instructions (Juknis). This study aims to evaluate the implementation of the KPPP technical guidelines in Solok Regency, specifically regarding pesticide supervision. The study used a qualitative approach with a phenomenological method, involving five key informants from the Department of Agriculture, the Department of Health, and the Department of Environment. Data were collected through focus group discussions (FGDs) and then analyzed using content analysis techniques. The results indicate that the implementation of the KPPP technical guidelines has not been optimal. Pesticide supervision still focuses on administrative verification without comprehensive field monitoring, and coordination across agencies has not been effectively established. This study emphasizes the need for institutional strengthening, increased resource capacity, and the establishment of an integrated monitoring and evaluation system to ensure more adaptive and accountable pesticide supervision.